Elevating Baby Care Category Relevance & Making Johnson's Baby As The Most Preferable Baby Toiletries Brand in Alfamart Through Integrated Shopper Path To Purchase Strategy - Frans, Jerry; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2015)
Abstract – Minimarket is the most important channel for FMCG Industry in Indonesia and considered as the main channel for urban shoppers. Alfamart is one of it which contribute 10% of J&J business and become number 1 retailer for J&J Indonesia. Alfamart quetioned the relevance of baby toiletries category in minimarket, they considered to stop selling the category in its stores. A shopper led category solution must be developed in order to turn around the business of baby toiletries in Alfamart. Shopper Study was made to understand shopper behaviour when shop baby toiletries in Alfamart. The methodology includes face- to- face exit interviews and qualitative accompanied shopping. The respondents were mothers with children 0-6 years old shopping for baby products at Alfamart. The study covers shopper demography, shopping mission, baby products browsed, engagement on the shelf, brand selection, as well as role of promotion. The strategy in general is explained using diamond strategy analysis described by Hambrick and Frederickson. And two kind of strategy are developed: Cooperative and Competitive Strategy. Competition and S.W.O.T. Analysis are made to complete the study and give whole perspective of business condition and situation. The recommendation includes category project in baby toiletries category of Alfamart with the objective to drive the relevance of the category for the Alfamart shopper. Some brand activation and promotion strategy also proposed to bring Johnson’s Baby become the number 1 brand of baby toiletries in Alfamart. Keywords: Minimarket, Baby Toiletries, Consumer Behavior, Category Management, Shopper Marketing.